Bayesian Estimation of the Parameter of the p-Dimensional Size-Biased Rayleigh Distribution - Rao, Arun Kumar; Pandey, Himanshu; Singh, Kusum Lata (Lithuanian Journal of Statistics, 2017)
In this paper, we have derived the probability density function of the size-biased p-dimensional Rayleigh distribution and studied its properties. Its suitability as a survival model has been discussed by obtaining its survival and hazard functions. We also discussed Bayesian estimation of the parameter of the size-biased p-dimensional Rayleigh distribution. Bayes estimators have been obtained by taking quasi-prior. The loss functions used are squared error and precautionary.
Keywords: Size-biased distribution; Bayes theorem; squared error loss function; precautionary loss function; quasi-prior